Change begets change: employing a change perspective to inform South Africa's coastal community conservation policy-praxis disjuncture - Rice, Wayne Stanley (Department of Environmental and Geographical Science, 2021)
Contemporary biodiversity conservation is ‘wickedly complex'. This complexity stems from the need to address the diverse objectives of protecting biodiversity and enhancing social wellbeing. However, centralized and exclusionary conservation approaches are often ill-suited to tackling these coupled objectives. Consequently, increasingly calls have been made for the development of more holistic, participatory, nuanced and context-specific conservation governance approaches. Community-based conservation – which seeks to include local communities and their knowledge and priorities in conservation governance – offers a viable though context-specific alternative. However, thus far communitybased conservation initiatives have produced mixed results, largely due to a lack of understanding of how to effectively initiate, implement and manage such ‘wickedly complex' conservation initiatives. South Africa possesses enabling legislation for community-based conservation, but to date there has been no implementation of legally recognized communityconserved areas in the coastal zone. Accordingly, this research is guided by a desire to better understand this ‘policy-praxis disjuncture', and explores what factors, conditions and processes are required to enable South Africa to embrace a more community-orientated approach to conservation. It is proposed that greater understanding and potentially success can be gained by viewing communitybased conservation including, the initiation, implementation and governance of community-conserved areas, as a ‘change process'. Drawing on Commons Theory, Governance Theory, and the Theory of Change approach, a framework was developed to guide the exploration of the factors, conditions and processes that enable the shift to a community-based mode of conservation governance. Case study investigations were conducted in two established regional community coastal conservation cases, and one South African ‘case-in-progress'. Based on the findings of these cases, and the perceptions of South African conservation actors, this dissertation offers insights for tackling South Africa's policy-praxis disjuncture by developing a South African Empirical Community-Based Conservation Theory of Change Pathway. By exploring the initiation, implementation and governance of community-based conservation initiatives as a change process, this dissertation provides a framework for designing a process to facilitate and implement community-based conservation where contextually appropriate. More specifically, it emphasizes the need to develop a context-appropriate, strategic, systematic and iterative set of actions, with clearly articulated assumptions, which strive to address present or potential issues, to support the change to community-based governance. Consequently, this dissertation provides a framework for understanding how a shift to a community-based mode of conservation governance takes place, and offers a South African specific design pathway, with potential application by diverse conservation actors in other countries.